P104: Emergency department opioid overdose study: prevalence of adverse outcomes. (15th May 2017) - Purssell, R.; Godwin, J.; Kestler, A.; Stenstrom, R.; DeWitt, C.; Scheuermeyer, F.X.; Balshaw, R.; Buxton, J.; Ho, V.; Brar, R.; Aquino, A.; Blackbourn, J.; et al.
Abstract : Introduction: The following adverse outcomes have been described in patients treated in hospital for opioid overdose: pulmonary edema, cardiac dysrhythmias, neurologic injury secondary to hypoxia, prolonged opioid toxicity, recurrent opioid toxicity. In addition, patients who take an overdose of fentanyl may develop fentanyl induced chest rigidity, a life-threatening complication that appears to be uniquely related to fentanyl. The prevalence of adverse outcomes and the clinical course of patients that develop these complications have been described in patients who have taken an overdose of heroin. However, in British Columbia there has been a dramatic increase in the number of patients who overdose on fentanyl and other ultrapotent opioids. The proportion of illicit drug overdose deaths in British Columbia for which fentanyl was detected was only 5% in 2012 but, by 2016, this proportion had increased to 62%. It is very important to know the prevalence of adverse outcomes and the clinical course of patients that develop these adverse outcomes in patients with an overdose of fentanyl or another ultrapotent opioid.Methods: We are completing a retrospective cohort study to evaluate the prevalence of the following adverse outcomes for patients treated in hospital for an opioid overdose: i) pulmonary edema, ii) cardiac dysrhythmias, iii) fentanyl induced chest rigidity, iv) neurologic injury secondary to hypoxia, v) prolonged opioid toxicity, vi) recurrent opioid toxicity. Health records of patients treated for opioid overdose in the emergency departments of six greater Vancouver hospitals from Jan 1, 2014 to Dec 31, 2016 are being reviewed.Results: All Institutional approvals have been obtained. The dataset of 3600 ED visits for opioid overdose has been obtained and 160 health records have now been reviewed as of January 8, 2017. We will describe the type and prevalence (with 95% confidence intervals) of complications sustained by these patients.Conclusion: The results of this study will guide management of opioid overdose in a setting were ultrapotent opioids are commonly ingested. All health records will have been reviewed and the data analysis completed by May 2017.